Participatory Leadership Innovation in Preserving Local Culture: Case Study of the Cultural Thursday Program at SDN Tua Nanga, Poto Tano District - Khaerul Azmi Risami; Muammar Khadafie (Golden Ratio of Mapping Idea and Literature Format, 2026)
Globalization has increasingly eroded local cultural values among younger generations, highlighting the need for primary education institutions to safeguard regional identity. In this context, participatory leadership by school principals plays a crucial role in promoting culturally grounded educational innovation. This study examines how participatory leadership supports cultural preservation through the Kamis Budaya (Cultural Thursday) Program at SDN Tua Nanga, West Sumbawa. Using a qualitative case study design, data were collected through observations, in-depth interviews with principals, teachers, students, and parents, and documentation of cultural activities. Data were analyzed through reduction, display, and conclusion drawing, with validity ensured via triangulation. The findings reveal that participatory leadership significantly contributes to the success of culture-based educational innovation. The principal acts as a facilitator, collaborator, and motivator, actively involving stakeholders in all program stages. The Kamis Budaya Program integrates local language, traditional attire, and folk arts into weekly learning activities, fostering students’ cultural pride, collaboration, and character development. However, challenges such as limited resources, weak institutional support, and lack of digital documentation persist. To address these, the school adopted strategies including cultural digitization, community partnerships, and curriculum integration. Overall, participatory leadership proves effective in sustaining local culture while preparing students for global challenges.